RECURRENT RESPIRATORY INFECTIONS IN CHILDREN AND THE PROGRAM IMMUNOREHABILITATION - Т. A. Chebotareva; L. N. Mazankova; A. P. Hoperskova; V. V. Malinovskaya; V. D. Koltsov; G. S. Bragina (LLC "Diagnostics and Vaccines", 2015)
The paper proposed a modern rehabilitation program for children with recurrent infections of the respiratory tract. As a result, it is shown interferon and immunotherapy is an important component of an integrated approach to the rehabilitation of children with recurrent respiratory infections, positively influencing to the nature of the immunological abnormalities. Using this scheme can reduce the frequency of episodes of ARI and increase the duration of clinically successful period after the experimentation.